2020
DOI: 10.1177/1473225420923761
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Children’s Resettlement (‘Reentry’) After Custody: Beyond the Risk Paradigm

Abstract: In response to policy concerns in England and Wales and internationally, a considerable knowledge base has identified factors statistically associated with reduced recidivism for children leaving custodial institutions. However, despite resulting guidance on how to support resettlement (‘reentry’), practice and outcomes remain disappointing. We argue that this failure reflects weaknesses in the dominant ‘risk paradigm’, which lacks a theory of change and undermines children’s agency. We conceptualise resettlem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(89 citation statements)
references
References 20 publications
0
57
0
Order By: Relevance
“…Partnership and collaboration between services and provision are also highlighted as significant when it comes to effectively addressing the causes of offending. This chimes with the original priorities of the pilot consortia as described above (Hazel et al, 2012).…”
Section: Resettling Young People: Partnership Working and Integrated mentioning
confidence: 66%
See 3 more Smart Citations
“…Partnership and collaboration between services and provision are also highlighted as significant when it comes to effectively addressing the causes of offending. This chimes with the original priorities of the pilot consortia as described above (Hazel et al, 2012).…”
Section: Resettling Young People: Partnership Working and Integrated mentioning
confidence: 66%
“…Similarly, research for the Prison Reform Trust (Jacobson et al, 2010) found that half of young people in custody came from deprived households, nearly 40% had been on the child protection register and/or had experienced abuse or neglect, and nearly half had been excluded from school. Furthermore, research (see Farrant, 2006; Gray, 2010) has shown that for many young people leaving custody, the wide range of problems that they were experiencing when they went into custody are simply exacerbated by the custodial sentence – in particular, the young person’s accommodation status (see Hazel et al, 2012).…”
Section: Resettling Young People: Partnership Working and Integrated mentioning
confidence: 99%
See 2 more Smart Citations
“…The fall in proven reoffending following a custodial disposal might be considered particularly surprising given that it is generally acknowledged, as noted above, that conditions in the children’s secure estate have deteriorated markedly in recent years and a range of commentaries point to a more challenging population in the secure estate (Bateman, 2016b; Green, 2019; Hazel and Lockwood, 2016; Her Majesty’s Inspector of Prisons for England Wales, 2018; Wood et al, 2017), with an escalation in already excessive levels of violence, self-harm, the use of restraint and isolation from peers. In the light of such evidence, any suggestion that improvements in the effectiveness of custodial provision might have contributed to lower rates of recidivism would appear to lack credibility.…”
Section: Making Sense Of the Data: Cautions And Incarcerationmentioning
confidence: 99%